Prescription drug overdose: between patients and their doctors - Ling W; Wu LT (Dove Medical Press, 2013)
Walter Ling,1 Li-Tzy Wu21Department of Psychiatry and Biobehavioral Science, Integrated Substance Abuse Programs, University of California, Los Angeles, CA, USA; 2Department of Psychiatry and Behavioral Sciences, Duke University Medical Center, Durham, NC, USAPrescription drug overdoses, mainly involving prescription opioids, have reached epidemic proportions in the United States over the past 20 years.1,2 Since 2003, prescription opioids have been involved in more drug-related overdose deaths than heroin and cocaine combined. Among patients who were prescribed opioids, an estimated 20% were prescribed high doses of opioids by either single or multiple physicians, and these patients appeared to account for the majority of prescription opioid-related overdoses.1,3,4 The increase in prescription overdose deaths has coincided with a major increase in prescription opioid sales.2 The prescribing practices of some physicians are often believed to have contributed in part to the increase in these overdose deaths. In a recently published perspective, Anna Lembke speculated on why doctors prescribe opioids to known prescription opioid abusers.5 Her article raises a timely and troubling issue for all of us interested in this area of medicine. Lembke identifies the root of the problem to lie in the changing societal attitude towards pain and suffering, the ever-growing availability of opioid medications, the regulatory requirements promulgated, and the perceived shift in the role of the medical professional in this context. Central to her argument is that physicians must now practice according to a set of externally imposed expectations of patients, payers, and regulators, putting the prescriber in the position of being "damned if you do and damned if you don’t". If Lembke is right, the physician now prescribes not according to what he or she wants to do, but according to what he or she must do. The result, at one extreme, is the patient acting as their own physician and, at the other extreme, self-deception on both ends. Things could hardly get worse. Lembke’s proposed solutions are to make the threat of public and legal censure equal in not treating addiction as in not treating pain, and to compensate addiction treatment on a par with care for other illnesses (presumably including pain).5